2016
DOI: 10.4236/ojmi.2016.62004
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Magnetic Particle Imaging for Monitoring the Effect of Magnetic Targeting

Abstract: Purpose: Magnetic targeting refers to the attachment of therapeutic agents to magnetizable particles such as magnetic nanoparticles (MNPs) and then applying magnetic fields to concentrate them to the targeted region such as solid tumors. The purpose of this study was to investigate the usefulness of magnetic particle imaging (MPI) for monitoring the effect of magnetic targeting using tumor-bearing mice. Materials and Methods: Colon-26 cells (1 × 10 6 cells) were implanted into the backs of eight-week-old male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…MPI is particularly useful because of the linear quantitation and lack of background signal, providing spatial information which allows the accurate monitoring of therapeutic agent delivery. 305 This information illustrates the quantity of drug delivered to the target site, as well as the drug dosage distribution within the body. The ability to track drug delivery also allows for real-time adjustment of ensuing doses, ensuring that the dosage at the target site remains within the patient's therapeutic window (Fig.…”
Section: Primary Biomedical Applications Of Mpimentioning
confidence: 99%
“…MPI is particularly useful because of the linear quantitation and lack of background signal, providing spatial information which allows the accurate monitoring of therapeutic agent delivery. 305 This information illustrates the quantity of drug delivered to the target site, as well as the drug dosage distribution within the body. The ability to track drug delivery also allows for real-time adjustment of ensuing doses, ensuring that the dosage at the target site remains within the patient's therapeutic window (Fig.…”
Section: Primary Biomedical Applications Of Mpimentioning
confidence: 99%
“…The ability to move particles with MPI for targeted drug delivery has also been presented. [13][14][15][16][17] Griese et al 18 have demonstrated how to simultaneously move and image micron-sized magnetic particles with the Magnetic Particle Imaging/Navigation (MPIN) method with a temporal arXiv:1906.07518v1 [physics.app-ph] 18 Jun 2019 resolution of 2.9 Hz. Micron-sized particles have been used to target endothelial cells of the central nervous system to identify over-expressed surface proteins such as ICAM-1.…”
Section: Introductionmentioning
confidence: 99%
“…6) Magnetic targeting has been developed for localizing drug carriers such as liposomes containing both MNPs and therapeutic agents in the targeted organ or tissue by applying external magnetic fields. 7) The magnetic targeting of therapeutic agents results in the concentration of the agents at the targeted site, consequently reducing or eliminating systemic unwanted side effects. 7) Recently, a new magnetic targeting strategy called "aerosol-based magnetic targeting" has been introduced for lung diseases.…”
mentioning
confidence: 99%
“…7) The magnetic targeting of therapeutic agents results in the concentration of the agents at the targeted site, consequently reducing or eliminating systemic unwanted side effects. 7) Recently, a new magnetic targeting strategy called "aerosol-based magnetic targeting" has been introduced for lung diseases. 8) Aerosol-based magnetic targeting uses magnetic aerosol droplets comprising nebulized MNPs and therapeutic agents.…”
mentioning
confidence: 99%